2019
DOI: 10.1002/ese3.405
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic flushing in soft coal sublayer: Gas extraction enhancement mechanism and field application

Abstract: In China, one or several ultrathin soft coal sublayers are widely developed in the coal seam. Therefore, a method of using hydraulic flushing in soft sublayer to enhance the gas extraction in these particular coal seams is developed in this work. We first established a new fully coupled gas extraction model by combing gas diffusion, gas flow, and a permeability model that considers the effect of stress change and plastic failure. By adopting this model, the gas extraction enhancement mechanism and its main inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…China is currently faced with the most severe gas disaster in coal mines in the world (Yuan 2016;Zhang et al 2019a; Xue and Yuan 2017). Gas pre-drainage is effective for coal mine gas control, and the the performance of sealing material is the key to ensuring drainage e ciency.…”
Section: Introductionmentioning
confidence: 99%
“…China is currently faced with the most severe gas disaster in coal mines in the world (Yuan 2016;Zhang et al 2019a; Xue and Yuan 2017). Gas pre-drainage is effective for coal mine gas control, and the the performance of sealing material is the key to ensuring drainage e ciency.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the soft and hard coals coexist in the coal seam, the prediction of coal and gas outburst is carried out according to these critical values, and it is found that the prediction index is not sensitive and the critical value is unreliable sometimes. Many coal seams in mines often contain soft and hard coal stratification. There are significant differences in mechanical characteristics and permeability between soft and hard coal. The mechanical strength of soft coal stratification is low, which is a prominent breakthrough point. Therefore, based on the difference of adsorption structure between soft and hard coal, it is of great significance to study the critical value of the inspection index for the regional outburst risk caused by the residual gas content when soft and hard coals coexist.…”
Section: Introductionmentioning
confidence: 99%
“…China is currently faced with the most severe gas disaster in coal mines in the world [1][2][3]. Gas predrainage is effective for coal mine gas control, and the performance of sealing material is the key to ensuring drainage efficiency.…”
Section: Introductionmentioning
confidence: 99%